2013
DOI: 10.1590/s1984-82502013000300023
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Care for hypertensive patients provided within the Family Health Strategy in Goiânia, Goiás, Brazil

Abstract: The aim of Pharmaceutical Care programs is to improve patients' quality of life, and such programs are particularly effective in the case of chronic diseases such as hypertension. The objective of this longitudinal study was to analyze a Pharmaceutical Care model for hypertensive patients receiving care within the Family Health Strategy (FHS). All patients were being seen by an FHS team affiliated to a primary healthcare unit in Goiânia, Goiás, Brazil. Fourteen patients participated in the study, with each pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 31 publications
2
15
0
10
Order By: Relevance
“…These results were shared by other studies that evaluated the effect of a pharmaceutical intervention on cardiovascular risk in other countries (Al Mazroui et al, 2009;Zhao et al, 2012;Amariles et al, 2012) and in Brazil (Lyra Junior et al, 2011;Firmino et al, 2012;Plaster, Melo, 2012;Martins, Aquino, 2013).…”
Section: Discussionsupporting
confidence: 67%
“…These results were shared by other studies that evaluated the effect of a pharmaceutical intervention on cardiovascular risk in other countries (Al Mazroui et al, 2009;Zhao et al, 2012;Amariles et al, 2012) and in Brazil (Lyra Junior et al, 2011;Firmino et al, 2012;Plaster, Melo, 2012;Martins, Aquino, 2013).…”
Section: Discussionsupporting
confidence: 67%
“…11 Há a proposta de uma lista não exaustiva e nem exclusiva de PRM, sendo estes sempre relacionados à necessidade, efetividade e segurança dos medicamentos. 26 27 Estas intervenções podem ser realizadas através de atuações na educação do doente, na estratégia farmacológica e na quantidade de medicamentos utilizando como via de comunicação a escrita doente/ doente-médico e a verbal doente/ doente-médico.…”
Section: Resultsunclassified
“…In a study carried out in Goiânia with hypertensive patients, we identified 10.1 drug-related problems per patient, and the most recurrent problem was ineffective treatment, and non-adherence was only the fourth most common issue (Martins et al, 2013). In a study conducted by Alano, Correa and Galato (2012) with patients monitored in a pharmaceutical care service of Santa Catarina, an average of 2.7 problems per patient were identified and the most common were related to the drugs' effectiveness and safety.…”
Section: Discussionmentioning
confidence: 99%